The Distinctiveness of "Gandeng Gendong" BALKONDES: A Critical Ethnographic Investigation of Community-Based Tourism Governance in the Borobudur Heritage Area - Pranoto; Muhammad Hatta (Jurnal Sains Terapan Pariwisata, 2026)
This study investigates the "Gandeng Gendong" (mutual support) strategy within the Village Economic Centres (BALKONDES) programme in the Borobudur heritage area as an innovative model of Community-Based Tourism (CBT). Drawing on eight months of critical ethnographic fieldwork across 20 BALKONDES in 20 villages of Borobudur District, Magelang Regency, Central Java, the research examines how communities construct meaning around collaborative tourism governance and how socio-economic transformation unfolds through centripetal and centrifugal mechanisms. Findings reveal that the "Gandeng Gendong" strategy, rooted in Javanese gotong royong (collective mutual aid), successfully creates a dual-level collaborative ecosystem: internal mechanisms that empower local communities within individual villages, and external mechanisms that foster inter-village resource sharing and collective marketing. Performance analysis of the 20 BALKONDES identifies three cluster typologies: Advanced, Developing, and Less Developed, shaped by leadership quality, community social capital, geographic accessibility, and state-owned enterprise (BUMN) support intensity. Despite meaningful achievements in livelihood diversification and social capital reconstruction, the model confronts significant sustainability challenges, particularly structural dependency on external corporate patronage and persistent tensions between collaborative solidarity and competitive market incentives. The study proposes a theoretical model of "Gandeng Gendong Distinctiveness" as a distinctive network-based CBT governance paradigm that integrates traditional Javanese values with contemporary institutional arrangements, offering transferable lessons for heritage tourism destinations across Southeast Asia.